Potential biomedical applications of renewable nanocellulose - de Souza, Sivoney F.; Cherian, Bibin M. [UNESP]; Leão, Alcides L. [UNESP]; Telascrea, Marcelo [UNESP]; Chaves, Marcia R. M.; Narine, Suresh S.; Sain, Mohini (Taylor & Francis, 2013)
Nanocellulose is observed to be a promising biomaterial for use as implants and scaffolds in tissue engineering. Due to their availability, high strength, low weight, and biodegradability, nanocellulose fibers can be used in several applications, including medicine and biomaterials such as scaffolds in tissue engineering, artificial skin and cartilage, and wound healing. Researchers are using nanocellulose to develop cartilage to create artificial outer ears. Designed studies were performed to apply nanocellulose as a blood vessel implant in humans and animals. Different strategies were developed to produce materials that use nanocellulose to apply to bone tissue engineering. Recently, the ability to cultivate nanocellulose on nerve cells is observed to be a vital achievement for many uses. Nanocellulose as an attractive fiber-reinforcing agent can present a viable material for the different kind of applications in the medical field, besides the relative low cost and ease of fabrication. With these inherent advantages of cellulose derivatives, some applications as hydrogels reinforced with cellulose appeared similar to natural tissue having hydrogel-like characteristics, which has the potential to replace materials for articular cartilage, mainly due to network structure, mechanical, viscoelastic, and swelling properties. Other applications of nanocellulose as scaffolds play a significant role in integrating the overall tissue constructs. Biocompatible nanocellulose material could potentially constitute an acceptable candidate in scaffolding of the tissue-engineered vessel due to the three-dimensional structure, controlled porosity and enhanced mechanical properties, surface adhesion capability, and increased extent of biodegradability. This chapter deals with the promising advancements made in the utilization of nanocellulose for the three main categories of biomaterials: inert, bioactive, and biodegradable materials. There is also an analysis of in vivo and in vitro research.